2014
DOI: 10.1002/app.41373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of montmorillonite on the rheological properties of dually crosslinked guar gum‐based hydrogels

Abstract: One strategy to create chemical and physical cross‐links simultaneously is to introduce into the chemical network hydrogen bonding with clay nanofillers. Understanding the relaxation mechanisms of these systems is crucially important and has drawn the extensive interest of many scientists. In this work, the influence of different amounts of montmorillonite on the structural and rheological properties of guar gum hydrogels was investigated. Depending on the clay content, different nanostructures were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 58 publications
3
15
0
1
Order By: Relevance
“…Aggregates of MTT particles are observed for higher concentrations, as shown by Figures (c,d) for H 2 and H 4 , respectively. Following the arguments of Branca et al . and the results in Figures and , it can be suggested that at lower concentrations (up to 1.0%) the MTT layers are fully and uniformly dispersed and exfoliated within the XG biopolymer matrix, whereas at higher concentrations MTT is present as composite‐tactoids.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Aggregates of MTT particles are observed for higher concentrations, as shown by Figures (c,d) for H 2 and H 4 , respectively. Following the arguments of Branca et al . and the results in Figures and , it can be suggested that at lower concentrations (up to 1.0%) the MTT layers are fully and uniformly dispersed and exfoliated within the XG biopolymer matrix, whereas at higher concentrations MTT is present as composite‐tactoids.…”
Section: Resultssupporting
confidence: 54%
“…The WAXD pattern for H 2 and H 4 exhibited a diffraction peak at the same 2θ value. Branca et al . studied guar gum‐MT hydrogels, obtaining similar WAXD patterns, where no intercalation occurred between the biopolymer chains and the clay particles.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, the contact of non‐modified polysaccharides with water provokes a fast swelling of the film and leads to their disintegration, making it impossible to determine their water uptake capacity [Figure (a‐)]. In contrast, the assembly of SEP and PALY to these polysaccharides significantly improves their water resistance due to their effect as physical crosslinking agents, analogously to that reported for montmorillonite sheets in a guar gum matrix, and the resulting films can maintain their integrity during and after the assay [Figure (a‐) and (a‐)]. Water absorption (pH 5.5) of the bionanocomposites as a function of the clay content is displayed in Figure (b,c).…”
Section: Resultsmentioning
confidence: 99%
“…However, due to great demands for tough hydrogels in various applications, improving the mechanical strengths of hydrogels has been an important topic over the last few decades. Nanocomposite hydrogels are identified to be a simple way of enhancing the mechanical properties of hydrogels through the addition of reinforcing organic/inorganic fillers such as Laponite, montmorillonite, and carbon nanotubes . So high tensile strength (up to 1.1 MPa) with high elongation (up to 800%) in Laponite‐based nanocomposite hydrogels is achieved .…”
Section: Introductionmentioning
confidence: 99%